Lack of neural contributions to the summating potential in humans with Meniere’s disease - Riggs, William J.; Fontenot, Tatyana E.; Hiss, Meghan M.; Varadarajan, Varun; Moberly, Aaron C.; Adunka, Oliver F.; Fitzpatrick, Douglas C. (Frontiers in Neuroscience, 2022)
Objective: To investigate the electrophysiology of the cochlear summating potential (SP) in patients with Meniere’s disease (MD). Although long considered a purely hair cell potential, recent studies show a neural contribution to the SP. Patients with MD have an enhanced SP compared to those without the disease. Consequently, this study was to determine if the enhancement of the SP was due to neural dysfunction. Design: Study participants included 41 adults with MD and 53 subjects with Auditory Neuropathy Spectrum Disorder (ANSD), undergoing surgery where the round window was accessible. ANSD is a condition with known neural dysfunction, and thus represents a control group for the study. The ANSD subjects and 17 of the MD subjects were undergoing cochlear implantation (CI) surgery; the remaining MD subjects were undergoing either endolymphatic sac decompression or labyrinthectomy to alleviate the symptoms of MD. Electrocochleography was recorded from the round window using high intensity (90 dB nHL) tone bursts. The SP and compound action potential (CAP) were measured to high frequencies (>=2 kHz) and the SP, cochlear microphonic (CM) and auditory nerve neurophonic (ANN) to low frequencies. Linear mixed models were used to assess differences between MD and ANSD subjects. Results: Across frequencies, the MD subjects had smaller alternating current (AC) response than the ANSD subjects (F=31.61,534, p<0.001), but the SP magnitudes were larger (F=94.31,534, p<0.001). For frequencies less than 4 kHz the SP magnitude in the MD group was significantly correlated with the magnitude of the CM (p’s<0.001) but not in the ANSD group (p’s>0.05). Finally, the relative proportions of both ANN and CAP were greater in MD compared to ANSD subjects. The shapes of the waveforms in the MD subjects showed the presence of multiple components contributing to the SP, including outer and inner hair cells and neural activity. Conclusions: The results support the view that the increased negative polarity SP in MD subjects is due to a change in the operating point of hair cells rather than a loss of neural contribution. The steady-state SP to tones in human subjects is a mixture of different sources with different polarities.